Proces oligarchizacji systemu partyjnego Ukrainy - Hurska-Kowalczyk, Liana (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: The process of „oligarchization” of the party system of Ukraine In this article the author try to analyze the process of growing into financial‑industrial groups in Ukraine’s political parties. She seeks to ascertain its causes and consequences. Analyzes the initial time of systemic transformations in Ukraine. Special attention is given to the time presidency of Leonid Kuchma (1994—2005), because he was the chief architect of the oligarchy of the economy and the political system of Ukraine. Key words: oligarchization, economy system, political system, systemic transformations, party system